Salivary Oxytocin Is Negatively Associated With Religious Faith in Japanese Non-Abrahamic People - Yamada, Junko; Nakawake, Yo; Shou, Qiulu; Nishina, Kuniyuki; Matsunaga, Masahiro; Takagishi, Haruto (Frontiers in Psychology, 2021)
Spirituality and religiosity have a significant impact of one’s well-being. Although previous studies have indicated that the neuropeptide hormone oxytocin is associated with spirituality/religiosity, existing findings remain inconsistent. Some studies have reported a positive relationship between oxytocin and spirituality/religiosity, while other studies reported a negative association. Herein, we examined the association between endogenous oxytocin and spirituality/religiosity in the 200 non-Abrahamic Japanese (102 females, mean age ± standard deviation = 41.53 ± 10.46) by measuring the level of salivary oxytocin and spiritual/religious faith. We found that the level of salivary oxytocin was negatively associated with spiritual/religious faith. Individuals with higher levels of salivary oxytocin tend to have more negative spiritual/religious faith compared to those with low oxytocin levels (e.g., “Spirituality/religiosity makes people passive and clinging.”). Moreover, this tendency were only significant in individuals who were not interested in a specific religion. The uniqueness of spirituality/religiosity in Japan could help interpret the current findings.